Removal Of Manganese (Mn) From Aqueous Solution Using Mixture Of Ferromanganese Ore And Humus - Kamal, Norinsafrina Mustaffa (2018)
This study examined effectiveness of mixture of ferromanganese ore (FMO) and humus to remove Mn from aqueous solution. Interactions between the FMO surface and humic substances from humus form complexation through ligand exchange, hydrogen bonding, hydrophobic interaction, etc. The complexation acts as additional binding sites thus provide more active surfaces for Mn adsorption. The methodology of this study had commenced with characterization of FMO and humus. Then, batch adsorption experiments were performed to evaluate effectiveness of FMO-humus mixture to remove Mn. Its performance was compared to the individual performance of the FMO and the humus. Furthermore, the batch experimental data was fitted to Langmuir and Freundlich isotherms to determine the best-fit model. Next, optimization study of the FMO-humus mixture was conducted by using Central Composite Design. Re-adsorption study was also performed to examine reusability of the media. Last analysis was a column study of FMO-humus mixture for determination of a breakthrough curve. Results from the adsorption experiments had shown FMO-humus mixture had slightly better performance compared to humus. Apart from that, Freundlich isotherm was the best-fit model towards all media with r2>0.9. Result from the optimization study of FMO-mixture had yielded 93.82% optimum removal of Mn. As for the re-adsorption study, FMO-humus mixture can be reused until 5 cycles with Mn removal of 92.25 to 95.22% without desorption treatment. Lastly, the breakthrough point and the exhaustion point for FMO-humus mixture of the column study were recorded on the 16th day and the 29th day respectively.